Organic silicon heat-conducting gel with high heat conductivity and preparation method thereof
By using modified diamond, aluminum nitride and modified carbon nanotubes as composite thermal fillers in thermal conductivity gels, and combining epoxy chain extenders to enhance the silicone oil system, the problem of increased hardness and insufficient thermal filler performance in the high-temperature thermal conductivity process is solved, and efficient thermal conductivity and good anti-aging properties are achieved.
Patent Information
- Application Number
- CN202411591464.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-08
AI Technical Summary
The hardness of existing thermal conductivity gels increases during high-temperature thermal conductivity, resulting in an increase in contact thermal resistance and a decrease in heat transfer effect. The intrinsic thermal conductivity of thermal fillers is low, the degree of interconnection with silicone oil is limited, and the aging resistance is poor, making it difficult to be suitable for heat dissipation of microelectronic devices.
Modified diamond, aluminum nitride and modified carbon nanotubes are used as composite thermal fillers, combined with components such as vinyl silicone oil, hydrogen-containing silicone oil and catalysts, and the cross-extension and cross-linking of the silicone oil system are enhanced through epoxy chain extenders to improve the stability and adhesion of thermally conductive silicone grease.
It significantly improves the thermal conductivity of the thermal gel, reduces the contact thermal resistance, ensures the cost and aging resistance of the material, and is suitable for efficient heat dissipation of microelectronic devices.
Smart Images

Figure BDA0005125695070000111
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of new materials and their application, and in particular to a highly thermally conductive organic silicone thermally conductive gel and a preparation method thereof. Background Art
[0002] With the development of industries such as thermal management in the large-scale application of new energy vehicle battery packs and 5G communication industries, higher efficiency has also greatly increased the working power per unit volume in electronic products, which has brought serious heat dissipation problems. The heat dissipation of electronic components will directly lead to the increase of electronic equipment temperature and thermal stress, posing a serious threat to the working reliability of microelectronic equipment. There is a very fine and uneven air gap between the microelectronic device and the radiator. The thermal conductivity of air is only 0.024W / mK, which is a poor conductor of heat. It will cause the contact thermal resistance between the electronic component and the radiator to be very large, which seriously hinders the conduction of heat and ultimately causes the radiator to be inefficient. Therefore, establishing an effective heat conduction channel between the electronic component and the radiator can greatly reduce the contact thermal resistance and give full play to the role of the radiator.
[0003] Thermally conductive gel is a thermal interface material with super high adaptability. Compared with thermally conductive gaskets, thermally conductive gel has excellent plasticity and can adapt to various irregular, variable-shaped and uneven heat dissipation interfaces, and its application scenarios are more flexible and varied. The thermally conductive gel on the market currently has the problem of increased hardness during high-temperature heat conduction, which leads to an increase in the contact thermal resistance with the interface during use and a significant reduction in the heat transfer effect. On the other hand, in order to obtain a higher thermal conductivity coefficient, more thermally conductive fillers are generally added to the resin system, but the conventional thermally conductive fillers have a low intrinsic thermal conductivity and a limited degree of interconnection between the thermally conductive fillers and silicone oil, resulting in a low filling rate. Due to the presence of a large amount of silicone oil between the thermally conductive fillers, the aging resistance is poor, and the thermal conductivity is not greatly improved. Summary of the invention
[0004] In view of the low intrinsic thermal conductivity of the thermally conductive filler in the existing thermally conductive gel, the limited degree of interconnection between the thermally conductive filler and the silicone oil, the poor aging stability, and the difficulty in being suitable for heat dissipation of microelectronic devices, the present application provides a high thermal conductivity silicone thermally conductive gel and a preparation method thereof.
[0005] In a first aspect, the present application provides a highly thermally conductive silicone thermally conductive gel, which adopts the following technical solution: A highly thermally conductive organic silicone thermally conductive gel comprises the following components in parts by mass: 16-20 parts of hydrogenated silicone oil, 28-35 parts of vinyl silicone oil, 0.3-0.6 parts of a catalyst, 0.2-0.5 parts of an inhibitor, 0.1-0.3 parts of an epoxy chain extender, and 79-94 parts of a composite thermally conductive filler; the composite thermally conductive filler comprises modified diamond, aluminum nitride, and modified carbon nanotubes.
[0006] By adopting the above technical scheme, modified diamond, aluminum nitride and modified carbon nanotubes are used as composite thermal conductive fillers, and a mixture of vinyl silicone oil, hydrogen-containing silicone oil, catalyst and epoxy chain extender is used as the matrix to prepare a highly thermally conductive silicone thermal conductive gel. The epoxy chain extender allows cross-stretching in the silicone oil system structure, enhancing the cross-linking with the polysiloxane network structure, thereby improving the stability of the thermal conductive silicone grease, achieving the regulation of the flow properties of the thermal conductive silicone grease, and also improving the adhesion of the thermal conductive silicone. Diamond, aluminum nitride and carbon nanotubes of different sizes and shapes with higher thermal conductivity are selected as composite thermal conductive fillers. Diamond as a thermal conductive filler has a higher thermal conductivity than conventional fillers, but the fluidity of diamond powder is poor and it cannot form a good thermal conductive path. On the one hand, carbon nanotubes have considerable thermal conductivity as a thermal conductive filler. On the other hand, the one-dimensional pore structure of carbon nanotubes can provide a better thermal conductive path for thermal conductive gel, making the thermal conductive gel have higher thermal conductivity. Aluminum nitride is added. The aluminum nitride particles are small and filled in the thermal conductive filler. Smaller particles can be distributed in the carbon nanotubes, which ensures the efficiency and stability of the thermal conductive filler filling, improves the uniformity of the internal components, eliminates the larger pores inside the single component of the thermal conductive gel, and improves the thermal conductivity of the thermal conductive gel. The influence of the characteristics of the three on the thermal conductivity is fully utilized, the thermal conductivity of the thermal conductive gel is significantly improved, and the cost and anti-aging of the thermal conductive gel material are guaranteed.
[0007] In addition, the modification of diamond and carbon nanotubes in the composite thermally conductive filler reduces the contact thermal resistance between the internal thermally conductive fillers, improves the viscosity and fluidity of the overall composite thermally conductive filler, and improves the thermal conductivity of the thermally conductive gel. Moreover, the modification of the thermally conductive filler increases the number of active functional groups, which can improve the compatibility with silicone oil, and can keep the thermally conductive gel stable for a long time without leakage. During the high-temperature heat conduction process, the interface thermal resistance is smaller, thereby avoiding the increase in the hardness of the thermally conductive gel and its adverse effects.
[0008] In a specific embodiment, the preparation method of the modified diamond comprises the following steps: taking diamond powder and adding it to an ethanol solution, ultrasonic grinding treatment, cleaning and drying, adjusting the temperature to 700-750°C and a low pressure of 100-105 kPa, and depositing in a CO2 atmosphere for 5-8 hours to obtain diamond; Take the bisaminosilane coupling agent and add it to anhydrous ethanol, dilute and mix it evenly with distilled water, hydrolyze it in a water bath at 30-38°C for 30-45min, add the above diamond with stirring, heat it to 60-70°C and react for 3-6h, then wash and dry it to obtain the modified diamond.
[0009] By adopting the above technical solution, the diamond powder is vapor deposited to remove impurities while improving the activity of the diamond surface, making it easier to graft and modify. More amino groups are on the diamond surface, which enhances the interface performance between the diamond and the silicone oil matrix and improves the cross-linking performance between the diamond and the matrix silicone oil.
[0010] In a specific embodiment, the mass ratio of the bisaminosilane coupling agent to diamond is (1.2-2.2):1.
[0011] Through a certain range of ratios of bisaminosilane coupling agent and diamond, the activated diamond surface is grafted with a certain number of amino groups with high activity that can be cross-linked with the silicone oil matrix. Too much bisaminosilane coupling agent leads to more grafting with epoxy groups, reducing the viscosity and flexible use performance of the thermal conductive silicone oil. A small amount of bisaminosilane coupling agent will deteriorate the surface performance of the diamond, affect the interface bonding properties with the silicone oil matrix, and affect the stable filling efficiency of the thermal conductive filler.
[0012] In a specific embodiment, the preparation method of the modified carbon nanotubes as hydroxyl-modified carbon nanotubes includes: adding carbon nanotubes to a mixed solution of sulfuric acid and nitric acid, heating to 70-75° C. for reaction, and obtaining modified carbon nanotubes.
[0013] By adopting the above technical solution, the hydroxyl group of carbon nanotubes is modified to enhance the compatibility of carbon nanotubes with modified diamonds, reduce the interface properties of carbon nanotubes with silicone oil matrix, and make it easier to mix with aluminum nitride, thereby reducing the contact thermal resistance between internal thermal conductive fillers and improving the thermal conductivity of thermal conductive gel.
[0014] In a specific embodiment, the mass ratio of sulfuric acid to nitric acid is 2:(3.2-5.1).
[0015] In a specific embodiment, the mass ratio of the modified diamond, aluminum nitride and modified carbon nanotube is 1:(5-8):(1:3).
[0016] By adopting the above technical scheme, modified diamond, aluminum nitride and modified carbon nanotubes are mixed and used in a certain proportion range, so that they have better bonding strength with the silicone oil matrix, provide certain viscosity and flow properties, and also make the thermal conductivity optimal within this quality range. Too much modified diamond will increase the hardness of the system, affect the flexibility of use of the thermal conductive gel, and reduce the bonding strength with the interface, affecting the filling rate, and then affecting the thermal conductivity. Too much modified carbon nanotubes will make the pores of the thermal conductive filler of the system too large, which will increase the thermal conductivity rate, but the thermal conductive gel is easily corroded by the outside world, the strength performance is weak, and the anti-aging performance deteriorates.
[0017] In a second aspect, the present application provides a method for preparing a highly thermally conductive silicone thermally conductive gel, using the following technical solution: A method for preparing a highly thermally conductive silicone thermally conductive gel comprises the following steps: Mix vinyl silicone oil and epoxy chain extender in a double planetary mixer at room temperature for 10-16 minutes, then add the composite thermal conductive filler, add the composite thermal conductive filler in batches, stir for 5-10 minutes after each addition until it is uniform, repeat the above steps until all the composite thermal conductive fillers are added, raise the temperature to 140-165°C, stir in vacuum, add hydrogen-containing silicone oil, inhibitor and catalyst, mix at room temperature for 30-40 minutes, and discharge to obtain thermal conductive gel.
[0018] The vacuum stirring is performed for 1-3 hours at a vacuum degree of -0.04-0.09 MPa and a rotation speed of 50-80 rpm.
[0019] The thermal conductive powder is first modified and then added to the silicone oil system in batches, which increases the coverage rate of the thermal conductive powder particle surface and has an excellent wetting effect, effectively improving the compatibility between the powder and the thermal conductive gel system. It also improves the stability and storage resistance of the thermal conductive silicone grease network structure.
[0020] In summary, this application has the following beneficial effects: 1. Using modified diamond, aluminum nitride and modified carbon nanotubes as composite thermal conductive fillers, and using a mixture of vinyl silicone oil, hydrogenated silicone oil, catalyst and epoxy chain extender as the matrix, a highly thermally conductive silicone thermal conductive gel is prepared. The epoxy chain extender allows cross-stretching in the silicone oil system structure, enhancing the cross-linking with the polysiloxane network structure, thereby improving the stability of the thermal conductive silicone grease, adjusting the flow properties of the thermal conductive silicone grease, and improving the adhesion of the thermal conductive silicone. Diamond, aluminum nitride and carbon nanotubes of different sizes and shapes with higher thermal conductivity are selected as composite thermal conductive fillers. Diamond as a thermal conductive filler has a higher thermal conductivity than conventional fillers, but the fluidity of diamond powder is poor and it cannot form a good thermal conductive path. On the one hand, carbon nanotubes have considerable thermal conductivity as a thermal conductive filler. On the other hand, the one-dimensional pore structure of carbon nanotubes can provide a better thermal conductive path for thermal conductive gel, making the thermal conductive gel have higher thermal conductivity. Aluminum nitride is added. The aluminum nitride particles are small and filled in the thermal conductive filler. Smaller particles can be distributed in the carbon nanotubes, which ensures the efficiency and stability of the thermal conductive filler filling, improves the uniformity of the internal components, eliminates the larger pores inside the single component of the thermal conductive gel, and improves the thermal conductivity of the thermal conductive gel. The influence of the characteristics of the three on the thermal conductivity is fully utilized, the thermal conductivity of the thermal conductive gel is significantly improved, and the cost and anti-aging of the thermal conductive gel material are guaranteed.
[0021] 2. Through a certain range of proportions of bisaminosilane coupling agent and diamond, the activated diamond surface is grafted with a certain number of amino groups with high activity that can be cross-linked with the silicone oil matrix. Too much bisaminosilane coupling agent leads to more grafting with epoxy groups, reducing the viscosity and flexible use performance of the thermal conductive silicone oil. A small amount of bisaminosilane coupling agent will deteriorate the surface performance of the diamond, affect the interfacial bonding properties with the silicone oil matrix, and affect the stable filling efficiency of the thermal conductive filler. DETAILED DESCRIPTION
[0022] The present application is further described in detail below with reference to the embodiments.
[0023] raw material Some of the raw materials used in the preparation examples and embodiments: bisaminosilane coupling agent model: KH-792; epoxy chain extender model: ADR-4370S; carbon nanotube (specification 2000-4000 mesh) model: NACODC8; aluminum nitride (specification 1um) model: PT-AlCN; diamond powder purchased from Zhengzhou Smelter Diamond Products; vinyl silicone oil with a viscosity of 1000mpa·s at room temperature, item number: LG-T1000; hydrogen-containing silicone oil with a viscosity of 50mpa·s, model SH-202; the catalyst is a Custer catalyst; the inhibitor is 1-ethynyl-1-cyclohexanol purchased from Guangdong Yuanfeng Chemical Reagent Co., Ltd.
[0024] The raw materials used in the examples and comparative examples that are not otherwise specified are all conventional products that can be purchased from the market.
[0025] Preparation Example Modified diamond preparation example Preparation Example 1 Take 1.5g of diamond powder and add it to 60ml of ethanol solution, ultrasonically grind it for 10min, wash it with 20ml of ethanol and blow it dry, adjust the temperature to 700℃ and 105KPa under a low pressure, and deposit it in a CO2 atmosphere for 5h to obtain diamond; take bisaminosilane coupling agent in proportion and add it to 50ml of anhydrous ethanol, dilute and mix it evenly with 30ml of distilled water, hydrolyze it in a water bath at 38℃ for 30min, stir and add diamond, the mass ratio of bisaminosilane coupling agent to diamond is 1.2:1; heat it to 60℃ and react for 6h, wash it with ethanol and dry it at 60℃ to obtain modified diamond.
[0026] Preparation Example 2 Take 1.5g of diamond powder and add it to 60ml of ethanol solution, ultrasonically grind it for 10min, wash it with 20ml of ethanol and blow it dry, adjust the temperature to 750℃ and a low pressure of 100KPa, and deposit it in a CO2 atmosphere for 8h to obtain diamond; take bisaminosilane coupling agent in proportion and add it to 50ml of anhydrous ethanol, dilute and mix it evenly with 30ml of distilled water, hydrolyze it in a water bath at 30℃ for 45min, stir and add diamond, the mass ratio of bisaminosilane coupling agent to diamond is 1.2:1; heat it to 70℃ and react for 3h, wash it with ethanol and dry it at 60℃ to obtain modified diamond.
[0027] Preparation Example 3 Take 1.5g of diamond powder and add it to 60ml of ethanol solution, ultrasonically grind it for 10min, wash it with 20ml of ethanol and blow it dry, adjust the temperature to 700℃ and 105KPa under low pressure, and deposit it in CO2 atmosphere for 5h to obtain diamond; take bisaminosilane coupling agent in proportion and add it to 50ml of anhydrous ethanol, dilute and mix it evenly with 30ml of distilled water, hydrolyze it in a water bath at 38℃ for 30min, stir and add diamond, the mass ratio of bisaminosilane coupling agent to diamond is 2.2:1; heat it to 60℃ and react for 6h, wash it with ethanol and dry it at 60℃ to obtain modified diamond.
[0028] Preparation Example 4 Take 1.5g of diamond powder and add it to 60ml of ethanol solution, ultrasonically grind it for 10min, wash it with 20ml of ethanol and blow it dry, adjust the temperature to 700℃ and 105KPa under low pressure, and deposit it in CO2 atmosphere for 5h to obtain diamond; take bisaminosilane coupling agent in proportion and add it to 50ml of anhydrous ethanol, dilute and mix it evenly with 30ml of distilled water, hydrolyze it in a water bath at 38℃ for 30min, stir and add diamond, the mass ratio of bisaminosilane coupling agent to diamond is 0.7:1; heat it to 60℃ and react for 6h, wash it with ethanol and dry it at 60℃ to obtain modified diamond.
[0029] Preparation Example 5 Take 1.5g of diamond powder and add it to 60ml of ethanol solution, ultrasonically grind it for 10min, wash it with 20ml of ethanol and blow it dry, adjust the temperature to 700℃ and 105KPa under low pressure, and deposit it in CO2 atmosphere for 5h to obtain diamond; take bisaminosilane coupling agent in proportion and add it to 50ml of anhydrous ethanol, dilute and mix it evenly with 30ml of distilled water, hydrolyze it in a water bath at 38℃ for 30min, stir and add diamond, the mass ratio of bisaminosilane coupling agent to diamond is 2.6:1; heat it to 60℃ and react for 6h, wash it with ethanol and dry it at 60℃ to obtain modified diamond.
[0030] Preparation example of modified carbon nanotubes Preparation Example 6 Take carbon nanotubes and add them into 100 ml mixed solution of sulfuric acid and nitric acid, the mass ratio of sulfuric acid to nitric acid is 2:3.2, heat to 75°C and react for 10 hours to obtain modified carbon nanotubes.
[0031] Preparation Example 7 Take carbon nanotubes and add them into 100 ml mixed solution of sulfuric acid and nitric acid, the mass ratio of sulfuric acid to nitric acid is 2:5.1, heat to 75°C and react for 10 hours to obtain modified carbon nanotubes.
[0032] Preparation Example 8 Take carbon nanotubes and add them into 100 ml mixed solution of sulfuric acid and nitric acid, the mass ratio of sulfuric acid to nitric acid is 1:1, heat to 75°C and react for 10 hours to obtain modified carbon nanotubes. Example
[0033] Example 1 A highly thermally conductive organic silicone thermally conductive gel comprises the following components in parts by weight: 20 g of hydrogenated silicone oil, 28 g of vinyl silicone oil, 0.6 g of a catalyst, 0.2 g of an inhibitor, 0.1 g of an epoxy chain extender, and 79 g of a composite thermally conductive filler; the composite thermally conductive filler is modified diamond and aluminum nitride prepared in Preparation Example 1 and modified carbon nanotubes prepared in Preparation Example 6, and the mass ratio of the modified diamond, aluminum nitride, and modified carbon nanotubes is 1:5:1.
[0034] Vinyl silicone oil and epoxy chain extender were mixed in a double planetary mixer at room temperature for 16 minutes, and then the composite thermal conductive filler was added. The composite thermal conductive filler was added in batches, and stirred for 5 minutes after each addition until it was uniform. The above steps were repeated until all the composite thermal conductive fillers were added. The temperature was raised to 165°C, the vacuum degree was -0.04MPa, and the speed was 80rpm. After vacuum stirring and mixing for 1 hour, hydrogen-containing silicone oil, inhibitor, and catalyst were added, and mixed at room temperature for 40 minutes. The thermal conductive gel was obtained.
[0035] Example 2 A highly thermally conductive organic silicone thermally conductive gel comprises the following components in parts by weight: 16 g of hydrogenated silicone oil, 35 g of vinyl silicone oil, 0.3 g of a catalyst, 0.5 g of an inhibitor, 0.3 g of an epoxy chain extender, and 94 g of a composite thermally conductive filler; the composite thermally conductive filler is modified diamond and aluminum nitride prepared in Preparation Example 1 and modified carbon nanotubes prepared in Preparation Example 6, and the mass ratio of the modified diamond, aluminum nitride, and modified carbon nanotubes is 1:5:1.
[0036] Vinyl silicone oil and epoxy chain extender were mixed in a double planetary mixer at room temperature for 10 minutes, and then the composite thermal conductive filler was added. The composite thermal conductive filler was added in batches, and stirred for 10 minutes after each addition until it was uniform. The above steps were repeated until all the composite thermal conductive fillers were added. The temperature was raised to 140°C, the vacuum degree was 0.09 MPa, and the speed was 50 rpm. After vacuum stirring and mixing for 3 hours, hydrogen-containing silicone oil, inhibitor, and catalyst were added, and mixed at room temperature for 30 minutes. The thermal conductive gel was obtained.
[0037] Example 3 A highly thermally conductive organic silicone thermally conductive gel comprises the following components in parts by weight: 16 g of hydrogenated silicone oil, 35 g of vinyl silicone oil, 0.3 g of a catalyst, 0.5 g of an inhibitor, 0.3 g of an epoxy chain extender, and 94 g of a composite thermally conductive filler; the composite thermally conductive filler is modified diamond and aluminum nitride prepared in Preparation Example 1 and modified carbon nanotubes prepared in Preparation Example 6, and the mass ratio of the modified diamond, aluminum nitride, and modified carbon nanotubes is 1:8:3.
[0038] Vinyl silicone oil and epoxy chain extender were mixed in a double planetary mixer at room temperature for 10 minutes, and then the composite thermal conductive filler was added. The composite thermal conductive filler was added in batches, and stirred for 10 minutes after each addition until it was uniform. The above steps were repeated until all the composite thermal conductive fillers were added. The temperature was raised to 140°C, the vacuum degree was 0.09 MPa, and the speed was 50 rpm. After vacuum stirring and mixing for 3 hours, hydrogen-containing silicone oil, inhibitor, and catalyst were added, and mixed at room temperature for 30 minutes. The thermal conductive gel was obtained.
[0039] Example 4 A highly thermally conductive organic silicone thermally conductive gel comprises the following components in parts by weight: 16 g of hydrogenated silicone oil, 35 g of vinyl silicone oil, 0.3 g of a catalyst, 0.5 g of an inhibitor, 0.3 g of an epoxy chain extender, and 94 g of a composite thermally conductive filler; the composite thermally conductive filler is modified diamond and aluminum nitride prepared in Preparation Example 1 and modified carbon nanotubes prepared in Preparation Example 6, and the mass ratio of the modified diamond, aluminum nitride, and modified carbon nanotubes is 3:6:3.
[0040] Vinyl silicone oil and epoxy chain extender were mixed in a double planetary mixer at room temperature for 10 minutes, and then the composite thermal conductive filler was added. The composite thermal conductive filler was added in batches, and stirred for 10 minutes after each addition until it was uniform. The above steps were repeated until all the composite thermal conductive fillers were added. The temperature was raised to 140°C, the vacuum degree was 0.09 MPa, and the speed was 50 rpm. After vacuum stirring and mixing for 3 hours, hydrogen-containing silicone oil, inhibitor, and catalyst were added, and mixed at room temperature for 30 minutes. The thermal conductive gel was obtained.
[0041] Example 5 A highly thermally conductive organic silicone thermally conductive gel comprises the following components in parts by weight: 16 g of hydrogenated silicone oil, 35 g of vinyl silicone oil, 0.3 g of a catalyst, 0.5 g of an inhibitor, 0.3 g of an epoxy chain extender, and 94 g of a composite thermally conductive filler; the composite thermally conductive filler is modified diamond and aluminum nitride prepared in Preparation Example 1 and modified carbon nanotubes prepared in Preparation Example 6, and the mass ratio of the modified diamond, aluminum nitride, and modified carbon nanotubes is 1:6:5.
[0042] Vinyl silicone oil and epoxy chain extender were mixed in a double planetary mixer at room temperature for 10 minutes, and then the composite thermal conductive filler was added. The composite thermal conductive filler was added in batches, and stirred for 10 minutes after each addition until it was uniform. The above steps were repeated until all the composite thermal conductive fillers were added. The temperature was raised to 140°C, the vacuum degree was 0.09 MPa, and the speed was 50 rpm. After vacuum stirring and mixing for 3 hours, hydrogen-containing silicone oil, inhibitor, and catalyst were added, and mixed at room temperature for 30 minutes. The thermal conductive gel was obtained.
[0043] Example 6 A highly thermally conductive organic silicone thermally conductive gel comprises the following components in parts by weight: 16 g of hydrogenated silicone oil, 35 g of vinyl silicone oil, 0.3 g of a catalyst, 0.5 g of an inhibitor, 0.3 g of an epoxy chain extender, and 94 g of a composite thermally conductive filler; the composite thermally conductive filler is modified diamond and aluminum nitride prepared in Preparation Example 2 and modified carbon nanotubes prepared in Preparation Example 6, and the mass ratio of the modified diamond, aluminum nitride, and modified carbon nanotubes is 1:5:1.
[0044] Vinyl silicone oil and epoxy chain extender were mixed in a double planetary mixer at room temperature for 10 minutes, and then the composite thermal conductive filler was added. The composite thermal conductive filler was added in batches, and stirred for 10 minutes after each addition until it was uniform. The above steps were repeated until all the composite thermal conductive fillers were added. The temperature was raised to 140°C, the vacuum degree was 0.09 MPa, and the speed was 50 rpm. After vacuum stirring and mixing for 3 hours, hydrogen-containing silicone oil, inhibitor, and catalyst were added, and mixed at room temperature for 30 minutes. The thermal conductive gel was obtained.
[0045] Example 7 A highly thermally conductive organic silicone thermally conductive gel comprises the following components in parts by weight: 16 g of hydrogenated silicone oil, 35 g of vinyl silicone oil, 0.3 g of a catalyst, 0.5 g of an inhibitor, 0.3 g of an epoxy chain extender, and 94 g of a composite thermally conductive filler; the composite thermally conductive filler is modified diamond and aluminum nitride prepared in Preparation Example 3 and modified carbon nanotubes prepared in Preparation Example 6, and the mass ratio of the modified diamond, aluminum nitride, and modified carbon nanotubes is 1:5:1.
[0046] Vinyl silicone oil and epoxy chain extender were mixed in a double planetary mixer at room temperature for 10 minutes, and then the composite thermal conductive filler was added. The composite thermal conductive filler was added in batches, and stirred for 10 minutes after each addition until it was uniform. The above steps were repeated until all the composite thermal conductive fillers were added. The temperature was raised to 140°C, the vacuum degree was 0.09 MPa, and the speed was 50 rpm. After vacuum stirring and mixing for 3 hours, hydrogen-containing silicone oil, inhibitor, and catalyst were added, and mixed at room temperature for 30 minutes. The thermal conductive gel was obtained.
[0047] Example 8 A highly thermally conductive organic silicone thermally conductive gel comprises the following components in parts by weight: 16 g of hydrogenated silicone oil, 35 g of vinyl silicone oil, 0.3 g of a catalyst, 0.5 g of an inhibitor, 0.3 g of an epoxy chain extender, and 94 g of a composite thermally conductive filler; the composite thermally conductive filler is modified diamond and aluminum nitride prepared in Preparation Example 4 and modified carbon nanotubes prepared in Preparation Example 6, and the mass ratio of the modified diamond, aluminum nitride, and modified carbon nanotubes is 1:5:1.
[0048] Vinyl silicone oil and epoxy chain extender were mixed in a double planetary mixer at room temperature for 10 minutes, and then the composite thermal conductive filler was added. The composite thermal conductive filler was added in batches, and stirred for 10 minutes after each addition until it was uniform. The above steps were repeated until all the composite thermal conductive fillers were added. The temperature was raised to 140°C, the vacuum degree was 0.09 MPa, and the speed was 50 rpm. After vacuum stirring and mixing for 3 hours, hydrogen-containing silicone oil, inhibitor, and catalyst were added, and mixed at room temperature for 30 minutes. The thermal conductive gel was obtained.
[0049] Example 9 A highly thermally conductive organic silicone thermally conductive gel comprises the following components in parts by weight: 16 g of hydrogenated silicone oil, 35 g of vinyl silicone oil, 0.3 g of a catalyst, 0.5 g of an inhibitor, 0.3 g of an epoxy chain extender, and 94 g of a composite thermally conductive filler; the composite thermally conductive filler is modified diamond and aluminum nitride prepared in Preparation Example 5 and modified carbon nanotubes prepared in Preparation Example 6, and the mass ratio of the modified diamond, aluminum nitride, and modified carbon nanotubes is 1:5:1.
[0050] Vinyl silicone oil and epoxy chain extender were mixed in a double planetary mixer at room temperature for 10 minutes, and then the composite thermal conductive filler was added. The composite thermal conductive filler was added in batches, and stirred for 10 minutes after each addition until it was uniform. The above steps were repeated until all the composite thermal conductive fillers were added. The temperature was raised to 140°C, the vacuum degree was 0.09 MPa, and the speed was 50 rpm. After vacuum stirring and mixing for 3 hours, hydrogen-containing silicone oil, inhibitor, and catalyst were added, and mixed at room temperature for 30 minutes. The thermal conductive gel was obtained.
[0051] Example 10 A highly thermally conductive organic silicone thermally conductive gel comprises the following components in parts by weight: 16 g of hydrogenated silicone oil, 35 g of vinyl silicone oil, 0.3 g of a catalyst, 0.5 g of an inhibitor, 0.3 g of an epoxy chain extender, and 94 g of a composite thermally conductive filler; the composite thermally conductive filler is modified diamond and aluminum nitride prepared in Preparation Example 1 and modified carbon nanotubes prepared in Preparation Example 7, and the mass ratio of the modified diamond, aluminum nitride, and modified carbon nanotubes is 1:5:1.
[0052] Vinyl silicone oil and epoxy chain extender were mixed in a double planetary mixer at room temperature for 10 minutes, and then the composite thermal conductive filler was added. The composite thermal conductive filler was added in batches, and stirred for 10 minutes after each addition until it was uniform. The above steps were repeated until all the composite thermal conductive fillers were added. The temperature was raised to 140°C, the vacuum degree was 0.09 MPa, and the speed was 50 rpm. After vacuum stirring and mixing for 3 hours, hydrogen-containing silicone oil, inhibitor, and catalyst were added, and mixed at room temperature for 30 minutes. The thermal conductive gel was obtained.
[0053] Embodiment 11 A highly thermally conductive organic silicone thermally conductive gel comprises the following components in parts by weight: 16 g of hydrogenated silicone oil, 35 g of vinyl silicone oil, 0.3 g of a catalyst, 0.5 g of an inhibitor, 0.3 g of an epoxy chain extender, and 94 g of a composite thermally conductive filler; the composite thermally conductive filler is modified diamond and aluminum nitride prepared in Preparation Example 1 and modified carbon nanotubes prepared in Preparation Example 8, and the mass ratio of the modified diamond, aluminum nitride, and modified carbon nanotubes is 1:5:1.
[0054] Vinyl silicone oil and epoxy chain extender were mixed in a double planetary mixer at room temperature for 10 minutes, and then the composite thermal conductive filler was added. The composite thermal conductive filler was added in batches, and stirred for 10 minutes after each addition until it was uniform. The above steps were repeated until all the composite thermal conductive fillers were added. The temperature was raised to 140°C, the vacuum degree was 0.09 MPa, and the speed was 50 rpm. After vacuum stirring and mixing for 3 hours, hydrogen-containing silicone oil, inhibitor, and catalyst were added, and mixed at room temperature for 30 minutes. The thermal conductive gel was obtained.
[0055] Comparative Example Comparative Example 1 A highly thermally conductive organic silicone thermally conductive gel comprises the following components in parts by weight: 16 g of hydrogenated silicone oil, 35 g of vinyl silicone oil, 0.3 g of a catalyst, 0.5 g of an inhibitor, 0.3 g of an epoxy chain extender, and 94 g of a composite thermally conductive filler; the composite thermally conductive filler is diamond, aluminum nitride, and modified carbon nanotubes obtained in Preparation Example 6, and the mass ratio of diamond, aluminum nitride, and modified carbon nanotubes is 1:5:1.
[0056] Vinyl silicone oil and epoxy chain extender were mixed in a double planetary mixer at room temperature for 10 minutes, and then the composite thermal conductive filler was added. The composite thermal conductive filler was added in batches, and stirred for 10 minutes after each addition until it was uniform. The above steps were repeated until all the composite thermal conductive fillers were added. The temperature was raised to 140°C, the vacuum degree was 0.09 MPa, and the speed was 50 rpm. After vacuum stirring and mixing for 3 hours, hydrogen-containing silicone oil, inhibitor, and catalyst were added, and mixed at room temperature for 30 minutes. The thermal conductive gel was obtained.
[0057] Comparative Example 2 A highly thermally conductive organic silicone thermally conductive gel comprises the following components in parts by weight: 16 g of hydrogenated silicone oil, 35 g of vinyl silicone oil, 0.3 g of a catalyst, 0.5 g of an inhibitor, 0.3 g of an epoxy chain extender, and 94 g of a composite thermally conductive filler; the composite thermally conductive filler is modified diamond, aluminum nitride, and carbon nanotubes prepared in Preparation Example 1, and the mass ratio of the modified diamond, aluminum nitride, and modified carbon nanotubes is 1:5:1.
[0058] Vinyl silicone oil and epoxy chain extender were mixed in a double planetary mixer at room temperature for 10 minutes, and then the composite thermal conductive filler was added. The composite thermal conductive filler was added in batches, and stirred for 10 minutes after each addition until it was uniform. The above steps were repeated until all the composite thermal conductive fillers were added. The temperature was raised to 140°C, the vacuum degree was 0.09 MPa, and the speed was 50 rpm. After vacuum stirring and mixing for 3 hours, hydrogen-containing silicone oil, inhibitor, and catalyst were added, and mixed at room temperature for 30 minutes. The thermal conductive gel was obtained.
[0059] Comparative Example 3 A highly thermally conductive organic silicone gel comprises the following components in parts by weight: 16 g of hydrogenated silicone oil, 35 g of vinyl silicone oil, 0.3 g of a catalyst, 0.5 g of an inhibitor, 0.3 g of an epoxy chain extender, and 94 g of a composite thermally conductive filler; the composite thermally conductive filler is modified diamond obtained in Preparation Example 1, and the mass ratio of aluminum nitride is 1:11.
[0060] Vinyl silicone oil and epoxy chain extender were mixed in a double planetary mixer at room temperature for 10 minutes, and then the composite thermal conductive filler was added. The composite thermal conductive filler was added in batches, and stirred for 10 minutes after each addition until it was uniform. The above steps were repeated until all the composite thermal conductive fillers were added. The temperature was raised to 140°C, the vacuum degree was 0.09 MPa, and the speed was 50 rpm. After vacuum stirring and mixing for 3 hours, hydrogen-containing silicone oil, inhibitor, and catalyst were added, and mixed at room temperature for 30 minutes. The thermal conductive gel was obtained.
[0061] Comparative Example 4 A highly thermally conductive organic silicone gel comprises the following components in parts by weight: 16 g of hydrogenated silicone oil, 35 g of vinyl silicone oil, 0.3 g of a catalyst, 0.5 g of an inhibitor, 0.3 g of an epoxy chain extender, and 94 g of a composite thermally conductive filler; the composite thermally conductive filler is the modified diamond prepared in Preparation Example 1 and the modified carbon nanotube prepared in Preparation Example 6, and the mass ratio of the modified diamond to the modified carbon nanotube is 1:11.
[0062] Vinyl silicone oil and epoxy chain extender were mixed in a double planetary mixer at room temperature for 10 minutes, and then the composite thermal conductive filler was added. The composite thermal conductive filler was added in batches, and stirred for 10 minutes after each addition until it was uniform. The above steps were repeated until all the composite thermal conductive fillers were added. The temperature was raised to 140°C, the vacuum degree was 0.09 MPa, and the speed was 50 rpm. After vacuum stirring and mixing for 3 hours, hydrogen-containing silicone oil, inhibitor, and catalyst were added, and mixed at room temperature for 30 minutes. The thermal conductive gel was obtained.
[0063] Comparative Example 5 A highly thermally conductive organic silicone thermally conductive gel comprises the following components in parts by weight: 16 g of hydrogenated silicone oil, 35 g of vinyl silicone oil, 0.3 g of a catalyst, 0.5 g of an inhibitor, 0.3 g of an epoxy chain extender, and 94 g of a composite thermally conductive filler; the composite thermally conductive filler is aluminum nitride and modified carbon nanotubes obtained in Preparation Example 6, and the mass ratio of aluminum nitride to the modified carbon nanotubes is 9:3.
[0064] Vinyl silicone oil and epoxy chain extender were mixed in a double planetary mixer at room temperature for 10 minutes, and then the composite thermal conductive filler was added. The composite thermal conductive filler was added in batches, and stirred for 10 minutes after each addition until it was uniform. The above steps were repeated until all the composite thermal conductive fillers were added. The temperature was raised to 140°C, the vacuum degree was 0.09 MPa, and the speed was 50 rpm. After vacuum stirring and mixing for 3 hours, hydrogen-containing silicone oil, inhibitor, and catalyst were added, and mixed at room temperature for 30 minutes. The thermal conductive gel was obtained.
[0065] Performance Testing The performance test of a high thermal conductivity silicone thermally conductive gel prepared in Examples 1-11 and Comparative Examples 1-5 was conducted using the following method: a. Thermal conductivity test: refer to ISO-CD22007-2 standard test; b. Viscosity: Refer to ASTM D4287 standard test; c. Hardness: Shore00 test; d. Anti-aging properties: Under the condition of the environment set at a temperature of 85°C and a humidity of 85%, the test body is subjected to an aging test for 1000 hours. This is mainly to test the limit that the thermal conductive silicone grease can withstand in the harsh environment of high temperature and high humidity. This is called double 85 aging for 1000 hours. The performance is shown in Table 1: Table 1 Performance test results As can be seen from Table 1, compared with Comparative Examples 1-5 and Example 2, the thermal conductivity, viscosity, hardness and anti-aging performance indicators of the thermally conductive gel prepared in Example 2 are all higher than those of Comparative Examples 1-5, indicating that the thermally conductive gel prepared by using modified diamond, aluminum nitride and modified carbon nanotubes as a composite thermally conductive filler has better efficacy, and the modification of diamond and carbon nanotubes in the composite thermally conductive filler reduces the contact thermal resistance between the internal thermally conductive fillers, improves the thermal conductivity of the overall composite thermally conductive filler, and avoids the hardness of the thermally conductive gel from increasing during high-temperature heat conduction. Diamond, aluminum nitride and carbon nanotubes of different sizes and shapes with higher thermal conductivity are selected as composite thermal conductive fillers. Diamond as a thermal conductive filler has a higher thermal conductivity than conventional fillers. The one-dimensional pore structure of carbon nanotubes can provide a better thermal conductive path for the thermal conductive gel, making the thermal conductive gel have higher thermal conductivity. Aluminum nitride is then added. The aluminum nitride particles are smaller and are filled in the thermal conductive filler. Smaller particles can be distributed in the carbon nanotubes, ensuring the efficiency and stability of the thermal conductive filler filling, improving the uniformity of the internal components, and improving the thermal conductivity of the thermal conductive gel.
[0066] Compared with Examples 2-5, it can be seen that the high thermal conductivity silicone thermal conductive gel prepared in Example 2 has better thermal conductivity, viscosity, hardness, anti-aging and other performance indicators than Examples 4-5. The applicant found that the modified diamond, aluminum nitride and modified carbon nanotubes disclosed in the present application are mixed and used in a proportion range, so that it has better bonding strength with the silicone oil matrix. Too much modified diamond will increase the hardness of the system and affect the flexibility of use of the thermal conductive gel, so that it has better bonding strength with the silicone oil matrix. Too much modified carbon nanotubes will make the thermal conductive gel easily corroded by the outside world, and the strength performance is weak, and the aging resistance performance deteriorates.
[0067] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A highly thermally conductive silicone gel, characterized in that: The invention comprises the following components in parts by weight: 16-20 parts of hydrogenated silicone oil, 28-35 parts of vinyl silicone oil, 0.3-0.6 parts of catalyst, 0.2-0.5 parts of inhibitor, 0.1-0.3 parts of epoxy chain extender and 79-94 parts of composite thermal conductive filler; the composite thermal conductive filler comprises modified diamond, aluminum nitride and modified carbon nanotubes.
2. The highly thermally conductive silicone gel according to claim 1, characterized in that: The preparation method of the modified diamond comprises the following steps: taking diamond powder and adding it to an ethanol solution, ultrasonic grinding treatment, cleaning and drying, adjusting the temperature to 700-750° C. and a low pressure of 100-105 kPa, and depositing in a CO2 atmosphere for 5-8 hours to obtain diamond; Take the bisaminosilane coupling agent and add it to anhydrous ethanol, dilute and mix it evenly with distilled water, hydrolyze it in a water bath at 30-38°C for 30-45min, add the above diamond with stirring, heat it to 60-70°C and react for 3-6h, then wash and dry it to obtain the modified diamond.
3. The high thermal conductivity silicone thermally conductive gel according to claim 2, characterized in that: The mass ratio of the bisaminosilane coupling agent to diamond is (1.2-2.2):
1.
4. The high thermal conductivity organic silicon thermally conductive gel according to claim 1, characterized in that: The preparation method of the modified carbon nanotubes as hydroxyl modified carbon nanotubes comprises: adding carbon nanotubes into a mixed solution of sulfuric acid and nitric acid, heating to 70-75° C. for reaction, and obtaining modified carbon nanotubes.
5. The high thermal conductivity silicone thermally conductive gel according to claim 1, characterized in that: The mass ratio of the sulfuric acid to the nitric acid is 2:(3.2-5.1).
6. The high thermal conductivity silicone thermally conductive gel according to claim 1, characterized in that: The mass ratio of the modified diamond, aluminum nitride and modified carbon nanotube is 1:(5-8):(1:3).
7. A method for preparing a highly thermally conductive silicone thermally conductive gel according to any one of claims 1 to 6, characterized in that: The following steps are involved: Mix vinyl silicone oil and epoxy chain extender in a double planetary mixer at room temperature for 10-16 minutes, then add the composite thermal conductive filler, add the composite thermal conductive filler in batches, stir for 5-10 minutes after each addition until it is uniform, repeat the above steps until all the composite thermal conductive fillers are added, raise the temperature to 140-165°C, stir in vacuum, add hydrogen-containing silicone oil, inhibitor and catalyst, mix at room temperature for 30-40 minutes, and discharge to obtain thermal conductive gel.
8. The method for preparing a highly thermally conductive silicone thermally conductive gel according to claim 7, characterized in that: The vacuum stirring is performed for 1-3 hours at a vacuum degree of -0.04-0.09 MPa and a rotation speed of 50-80 rpm.
Citation Information
Patent Citations
Heat-conducting gel and preparation method thereof
CN111777994A
Heat-conducting gel and preparation method thereof
CN114292521A
Heat-conducting gel for battery filling and preparation process of heat-conducting gel
CN115850975A
Preparation process of low-viscosity low-modulus high-thermal-conductivity single-component gel
CN115960463A